2010
DOI: 10.1037/a0019390
|View full text |Cite
|
Sign up to set email alerts
|

Perceiver effects as projective tests: What your perceptions of others say about you.

Abstract: In 3 studies, we document various properties of perceiver effects-or how an individual generally tends to describe other people in a population. First, we document that perceiver effects have consistent relationships with dispositional characteristics of the perceiver, ranging from self-reported personality traits and academic performance to well-being and measures of personality disorders, to how liked the person is by peers. Second, we document that the covariation in perceiver effects among trait dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
182
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(209 citation statements)
references
References 50 publications
15
182
0
Order By: Relevance
“…We argued that narcissists disregard others' advice due to their lack of concern for others. That is, narcissists believe others are less competent and reflective (Kernis & Sun, 1994;Wood, Harms, & Vazire, 2010). It remains unclear based on Study 2's findings whether this is the reason for the lower perceived usefulness of advice.…”
Section: Resultsmentioning
confidence: 67%
“…We argued that narcissists disregard others' advice due to their lack of concern for others. That is, narcissists believe others are less competent and reflective (Kernis & Sun, 1994;Wood, Harms, & Vazire, 2010). It remains unclear based on Study 2's findings whether this is the reason for the lower perceived usefulness of advice.…”
Section: Resultsmentioning
confidence: 67%
“…This is not entirely unexpected. That deeply held perceptions or schemas of others have important interpersonal consequences is well established (Wood et al 2010). Once a team political climate has formed, members are likely to attribute ambiguous behaviors of others as potentially threatening and react accordingly.…”
Section: Discussionmentioning
confidence: 98%
“…However, loneliness and depressive symptoms are internal and subjective processes, which are most appropriately investigated with self-report measures. With respect to personality traits, other-reported measures could be used, although a recent study showed that these measures might be as informative about the raters' personality as they are about the personality of the person being rated (Wood et al 2010). Third, personality traits were measured only at baseline in the present study.…”
Section: Limitations and Conclusionmentioning
confidence: 95%